A Novel Runtime Monitoring Architecture - Nelissen, Geoffrey (2015)
Poster presented in 28th GI/ITG International Conference on Architecture of Computing Systems (ARCS 2015). 25 to 28, Mar, 2015, Poster Session. Porto, Portugal.